Protective effect of a recombinant vaccine against hepatitis B following three immunization schema - Marocho, Luis (2006)
Objective: To demonstrate that the protective effect against hepatitis B in susceptible health sciences students is similarly achieved following completion of three vaccination schema, one conventional and two shortened in time and doses. Design: Analytical, experimental, longitudinal, prospective, and concurrent cohorts study. Materials and Methods: The study was performed in 89 last year (internship) Medical Technology students of both sexes and less than 30 year-old, from the Professional Academy School, Faculty of Medicine, San Marcos University. They were distributed in three vaccine receptors groups: one conventional at 0, 1, and 6 months, and two shortened to 0 and 1 month or 0, 1 and 2 months. We excluded those students vaccined against hepatitis B and those positive to surface antigen markers (HBsAg) or total anti core (anti-HBc IgG). According to the cronograme established, we administered the hepatitis B virus recombinant vaccine (REVACB) at 20 mcg/mL concentrations and blood samples were obtained for antibody levels. Results: Average students age was 23,5 yearold, 51,7% (46) were male and 48,3% (43) female. At 30 days from the first dose, 12,4% showed protection; at 30 days post second dose, 98,8%, and at 180 days, 100% obtained protection. Conclusions: Protective effect against hepatitis B was obtained by three different vaccination schema: conventional (three doses), shortened (two doses), and shortened (three doses). We propose the possibility of administering the two doses plan with less cost and same benefit.